Grimm Legacies : The Magic Spell of the Grimms' Folk and Fairy Tales - Zipes, Jack, 1937- (Book collections on Project MUSE., 2015)
"In Grimm Legacies, esteemed literary scholar Jack Zipes explores the legacy of the Brothers Grimm in Europe and North America, from the nineteenth century to the present. Zipes reveals how the Grimms came to play a pivotal and unusual role in the evolution of Western folklore and in the history of the most significant cultural genre in the world--the fairy tale. Folklorists Jacob and Wilhelm Grimm sought to discover and preserve a rich abundance of stories emanating from an oral tradition, and encouraged friends, colleagues, and strangers to gather and share these tales. As a result, hundreds of thousands of wonderful folk and fairy tales poured into books throughout Europe and have kept coming. Zipes looks at the transformation of the Grimms' tales into children's literature, the Americanization of the tales, the "Grimm" aspects of contemporary tales, and the tales' utopian impulses. He shows that the Grimms were not the first scholars to turn their attention to folk tales, but were vital in expanding readership and setting the high standards for folk tale collecting that continue through the current era. Zipes concludes with a look at contemporary adaptations of the tales and raises questions about authenticity, target audience, and consumerism. With erudition and verve, Grimm Legacies examines the lasting universal influence of two brothers and their collected tales on today's storytelling world."--